The perils of global legalism - Posner, Eric A., 1965- (Chicago, [Ill.] ; London : University of Chicago Press, 2009)
The first months of the Obama administration have led to expectations, both in the US and abroad, that in the coming years America will increasingly promote the international rule of law - a position that many believe is both ethically necessary and in the nation's best interests. With 'The Perils of Global Legalism', Eric A. Posner explains that such views demonstrate a dangerously naive tendency toward legalism - an idealistic belief that law can be effective even in the absence of legitimate institutions of governance.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International law -- Philosophy; International relations; International and municipal law; Law; Politics & government; Law & society, sociology of law; International law